Study of vector antennas - Zeng, Yong (2009)
Direction of arrival (DOA) estimation for electromagnetic waves has its wide application in today’s industry and it has attracted a lot of research interest in the past several decades. Traditional DOA estimation techniques usually use antenna arrays as field sensors, whose data outputs are scalar quantities. Such techniques can give relatively good performance if many antenna elements are used. However, when the number of antenna elements used is relatively small, the performance degrades dramatically due to the poor accuracy and low resolution. Besides, if linear antenna arrays are used as field sensors, the ambiguity problems make it impossible to estimate the entire 360⁰ ranges. In order to solve such problems, instead of traditional antenna arrays, vector antennas can be used as field sensors. Since the technique of source localization using vector sensors was proposed in 1991, many vector antenna configurations as well as estimation algorithms have been designed and proposed. Study has shown that DOA estimation using vector sensors outperforms that using traditional antenna arrays. This project mainly studied vector antennas in DOA estimations. Theoretical analysis and software simulations are the two main methodologies for the project. The simulation uses Numerical Electromagnetics Code (NEC) as the engine for antenna response to the electromagnetic wave excitations, MATLAB for the signal processing and HFSS (High Frequency Structural Simulator) for structure modelling. Several antenna configurations with the aim to provide DOA estimation with high accuracy, high resolution, and the widest estimation range using the least number of elements are designed and the corresponding algorithms are proposed. Simulation results have shown that vector antennas, when properly designed and processed, can provide very good performances, which is unattainable by using traditional antenna arrays with the same number of elements. After a series of comparison and analysis, a DOA estimation technique based on MUSIC algorithm by using four-loop distributed vector antenna (DVA) array is recommended.